DISCOVERING THE FALSE OF THE HADITHS ABOUT SUFISM IN THE BOOK OF NASAIHUL IBAD BY SYEKH NAWAWI AL-BANTANI, INDONESIA - Masrukhin Mushin; Mila Amelia (CV. Radja Publika, 2026)
This article explains the quality of the hadiths about Sufism in the book Nashaihul Ibad by Sheikh Nawawi al-Bantani, especially those related to maqamat and ahwal. The type of research in this article is qualitative research. Research sources in this article are divided into primary and secondary sources. The primary source is the book Nashaihul Ibad by Sheikh Nawawi al-Bantani. Meanwhile, the analysis method uses the takhrij hadith method. This research found that there are four terms included in the criteria for maqamat and ahwal, namely: repentance, asceticism, patience and makrifat. Of the four terms, there are two hadiths about repentance and one hadith about asceticism, while the other three hadiths have no sanad path or no source found. As for the quality of the hadiths about Sufism, especially about maqamat and ahwal in the book Nashaihul Ibad by Sheikh Nawawi al-Bantani, many of them are of the quality of dha'if (weak), matruk al-Hadith and some even reach the level of maudhu' (fake). This research has implications for the vigilance of Muslims in receiving information regarding the quality of hadith about Sufism in the Nasaihul Ibad book, especially those related to maqamat and ahwal. The author recommends that other researchers conduct research related to the hadiths in the book Nasaihul Ibad with different themes.